(untitled) (Revista de História Regional, 2007)
The aim of this paper is to discuss the rebuilding process of the urban space of Guarapuava in relation to the social and economical transformations of the region. To the understanding of the local space the inter-relation of the scales of analysis will be used to indicate the most important moments of the transformation of the division and the articulation of the work between the regional and local space reflected in the rearrangement of their functions and forms.